IMPLICATIONS OF SOCIAL CAPITAL ON AGRICULTURAL DIGITAL MARKETING IN MEZAM DIVISION, CAMEROON - Ngum, R.; Bime, M. E.; Tambi, D. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed the implications of social capital on agricultural digital marketing in Mezam division, Cameroon. The objectives targeted are to: determine the drivers of social capital, evaluate the influence of social capital on agricultural digital marketing and discuss the gender differences in the effects of social capital on agricultural digital marketing relationship. Methodologically, the study made used of primary data, obtained among 400 agropreneurs using a wee-structured questionnaire and via a snowball sampling technique. The result is analyse using the ordinary least squared technique. The result shows that social capital is observed to be positive and strongly corroborating with agricultural digital marketing with a magnitude of 10.22% at 5% significance level. The result by gender shows that the relationship between social capital and agricultural digital marketing is more of female gender phenomenon than male counterpart. The result suggests that to enhance agricultural digital marketing, the decision makers in the agricultural sector should encourage social networking and cohesion among agropreneurs in Mezam division and Cameroon in general. This is an important step towards achieving sustainable development goals number two of the United Nations Organization.